Intravenously Injected Amyloid-β Peptide With Isomerized Asp7 and Phosphorylated Ser8 Residues Inhibits Cerebral β-Amyloidosis in AβPP/PS1 Transgenic Mice Model of Alzheimer’s Disease - Kozin, Sergey A.; Barykin, Evgeny P.; Telegin, Georgy B.; Chernov, Alexander S.; Adzhubei, Alexei A.; Radko, Sergey P.; Mitkevich, Vladimir A.; Makarov, Alexander A. (Frontiers in Neuroscience, 2018)
Cerebral beta -amyloidosis, an accumulation in the patient’s brain of aggregated amyloid-beta (Abeta) peptides abnormally saturated by divalent bio metal ions, is one of the hallmarks of Alzheimer’s disease (AD). Earlier, we have found that exogenously administrated synthetic Abeta with isomerized Asp7 (isoD7- Abeta) induces Abeta fibrillar aggregation in transgenic mice model of AD. IsoD7- Abeta molecules have been implied to act as seeds enforcing endogenous Abeta to undergo pathological aggregation through zinc-mediated interactions. On the basis of our findings on zinc-induced oligomerization of metal-binding domain of various Abeta species, we hypothesize that upon phosphorylation of Ser8 isoD7-Abeta loses its ability to form zinc-bound oligomeric seeds. Here we have found that (i) in vitro isoD7- Abeta with phosphorylated Ser8 (isoD7-pS8-Abeta) is less prone to spontaneous and zinc-induced aggregation in comparison with isoD7- Abeta and intact Abeta as shown by thioflavin T fluorimetry and dynamic light scattering data, and and (ii) intravenous injections of isoD7-pS8-Abeta significantly slow down progression of institutional beta-amyloidosis in APP/PS1 transgenic mice as shown by reduction of congophilic amyloid plaques’ number in hippocampus. The results support the role of the zinc-mediated oligomerization of Abeta species in modulation of cerebral beta-amyloidosis and demonstrate that isoD7-pS8-Abeta can serve as a potential molecular tool to block aggregation of endogenous Abeta in AD.